Evaluation of the colour properties of CdTe PV windows. (February 2019) - Liu, Dingming; Sun, Yanyi; Liu, Xiao; Wilson, Robin; Wu, Yupeng
Abstract: Building-Integrated Photovoltaic Window can potentially improve building energy efficiency. However, with the integration of solar cells, the colour properties of daylight passing through PV windows may be affected. It is important to explore the colour properties of the transmitted daylight to ensure a comfort luminous environment for its occupants. In this study, the spectral transmittances of four types CdTe PV window have been measured, subsequently the colour properties of the tested windows are examined and evaluated by Correlated Colour Temperature (CCT) and Colour Rendering Index (CRI). It was found that CdTe PV windows can achieve recommended CCT (i.e. 3300-5000K) when the daylight source is in the range of 4000K and 6500K. The general CRI of all the CdTe PV windows can be maintained in a comfort range, which is higher than 90, under different daylight scenarios.